2018
DOI: 10.1108/ijshe-11-2016-0214
|View full text |Cite
|
Sign up to set email alerts
|

Educating academic staff to reorient curricula in ESD

Abstract: Purpose The purpose of this paper is to present a professional development experience for higher education academic staff within the framework of an international Tempus project focused on reorienting university curricula to address sustainability. The project included revising curricula to phase sustainable development principles into university courses. Design/methodology/approach A qualitative approach was used to examine perceived professional development. Focus groups have been conducted with the academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 26 publications
6
61
0
5
Order By: Relevance
“…In higher education, we may be able to train future teachers in value reflection and try to transform them to more sustainable ways of living and teaching [140]. Of course these changes also require academic staff development in universities, which could for example be initiated by curricular changes towards ESD, as a qualitative study showed [141]. Such a curricular change might explicitly include ethics and the reflection of own values [142].…”
Section: Discussionmentioning
confidence: 99%
“…In higher education, we may be able to train future teachers in value reflection and try to transform them to more sustainable ways of living and teaching [140]. Of course these changes also require academic staff development in universities, which could for example be initiated by curricular changes towards ESD, as a qualitative study showed [141]. Such a curricular change might explicitly include ethics and the reflection of own values [142].…”
Section: Discussionmentioning
confidence: 99%
“…We continue to meet monthly as a team of instructors, to reflect on and improve the course, including ways to encourage diverse perspectives in class discussions. Prior work has shown that collaborative curriculum planning for EfS can help instructors reflect on and improve their teaching [59].…”
Section: Motivationmentioning
confidence: 99%
“…In the case of Secondary Education, some studies [35] worked with a group of 15-16-year olds to incorporate and apply STSE knowledge to an uncontrolled dumping of waste in order to explain to the students the social and environmental repercussions it entailed. Conversely, some studies at a university level [36] analysed the perspective with which sustainability is approached in higher education degrees [37,38]. Specifically, these authors structured teaching-learning problems with a methodology approached through a SWOT analysis.…”
Section: Introductionmentioning
confidence: 99%